Improvement of the Nature of Indentation Size Effect of Bi-2212 Superconducting Matrix by Doped Nd Inclusion and Theoretical Modeling of New Matrix - Ozturk, O.; Asikuzun, E.; Kaya, S.; Yildirim, G.; Turkoz, M. B.; Kilic, A. (Springer Science and Business Media LLC, 2014)
Neodmium (Nd) inclusions at different stoichiometric ratios (x=0.0, 0.001 %, 0.005 %, 0.01 %, 0.05 %, 0.1 %) are doped in the Bi-2212 superconducting samples and the samples obtained are subjected to the sintering process at 840 ∘C constant temperature for 72 hours. The effect of Nd doping on the structural and mechanical properties of prepared samples is investigated by the standard characterization measurements. XRD and SEM measurements are performed to obtain information about surface morphology, phase ratios, lattice parameters and particle size. Moreover, Vickers microhardness (H V ) measurements are exerted to investigate the mechanical properties of the all samples in detail. It is found that all the properties given above retrogress with the increase of the Nd concentration in the Bi-2212 superconducting core. However, the ISE nature of the materials improves systematically. Additionally, the experimental results of microhardness measurements are analyzed using Meyer’s law, PSR, MPSR, EPD models and HK approach. The results show that Hays–Kendall approach is determined as the most successful model.
Keywords: Meyer's law; HK approach; Meyer's Law; XRD; SEM; HK Approach; ISE; 10. No inequality